Pro HTML5 and CSS3 design patterns - Bowers, Michael (Apress, 2011)
Pro HTML5 and CSS3 Design Patterns is a reference book and a cookbook on how to style web pages using CSS3 and HTML5. It contains 350 ready to use patterns (CSS3 and HTML5 code snippets) that you can copy and paste into your code. Each pattern can be combined with other patterns to create an unlimited number of solutions, and each pattern works reliably in all major browsers without the need for browser hacks. The book is completely up-to-date with code, best practices, and browser compatibilities for HTML5 and CSS3?enabling you to dive in and make use of these new technologies in production environments. Pro HTML5 and CSS3 Design Patterns is so much more than just a cookbook, though! It systematically covers every usable feature of CSS3 and combines these features with HTML5 to create reusable patterns. Each pattern has an intuitive name to make it easy to find, remember, and refer to. Accessibility and best practices are carefully engineered into each design pattern, example, and source code. The book's layout, with a pattern's example on the left page and its explanation on the right, makes it easy to find a pattern and study it without having to flip between pages. The book is also readable from cover to cover, with topics building carefully upon previous topics. Pro HTML5 and CSS3 Design Patterns book unleashes your productivity and creativity in web design and development. Instead of hacking your way toward a solution, you'll learn how to predictably create successful designs every time by reusing and combining modular design patterns.